Degradation of crude oil and utilization of hydrocarbon compounds by bacterial isolates from used engine oil-contaminated soil and detection of the hydrocarbon-degrading genes - Nicdao, Michael Angelo C.; Rivera, Windell L. (Quezon City Institute of Biology, College of Science, University of the Philippines Diliman, 2009)
Two strains of Gordonia species and Gordonia terrae were isolated from soil sample contaminated with engine oil using mineral salt medium (MSM). The samples were obtained from a motor shop in Magalang, Pampanga, Philippines.
Thesis (M.S. Microbiology)--University of the Philippines Diliman
Keywords: Biodegradation; Petroleum -- Biodegradation